2018
DOI: 10.1590/1807-3107bor-2018.vol32.0117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of untreated dental caries on oral health-related quality of life of children with special health care needs

Abstract: The oral health status of children with special health care needs (SHCN) can affect their quality of life wich domains of the Brazilian version of the Early Childohood Oral Health Impact Scale (B-ECOHIS). A cross-sectional study was conducted in children with SHCN (aged 1 to 9 years), who underwent an oral examination for the assessment of dental caries severity. Parents/caregivers answered two questionnaires, one on oral health-related quality of life (OHRQoL)-B-ECOHIS, and one on socioeconomic characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 27 publications
5
28
2
2
Order By: Relevance
“…Similar to findings of this study, the most frequently reported impacts were 'pain in the teeth, mouth, or jaws' [35] and the associated pain from dental caries has a negative impact on children's emotional status, sleep patterns, and ability to learn or perform their usual activities [2]. Another study conducted among children and adolescents found a high dental caries experience and that dental caries had a negative impact on OHRQoL [12].…”
Section: Discussionsupporting
confidence: 81%
“…Similar to findings of this study, the most frequently reported impacts were 'pain in the teeth, mouth, or jaws' [35] and the associated pain from dental caries has a negative impact on children's emotional status, sleep patterns, and ability to learn or perform their usual activities [2]. Another study conducted among children and adolescents found a high dental caries experience and that dental caries had a negative impact on OHRQoL [12].…”
Section: Discussionsupporting
confidence: 81%
“…These results are in agreement with Pani et al [4] and Richa et al [5]. has been reported in the literature [4,5,7,8,[17][18][19][20][21][22][23][24]. The impact observed in the present study was high, but higher impact was on caries-free children in the SWB domain.…”
Section: Discussionsupporting
confidence: 94%
“…The index does not represent only an untreated lesion. Individuals with special needs with dental (experience untreated caries) are more likely to suffer high negative impact on their OHRQoL than those without dental caries experience [24]. Parents reported more problems in the OHRQoL of their children when the untreated lesion was considered [24] or in the case of severe caries [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental caries is one of the most prevalent oral disease in children which can result in significant discomfort, pain and affects them psychologically. [1][2][3][4] Dental caries also places a financial burden on parents as well as health care system of a country. Sound oral health is mandatory for mastication, phonation and provides an acceptable appearance which aid in early social contacts and is the basis of sustained oral health all the way through infancy into adolescence and adulthood.…”
Section: Introductionmentioning
confidence: 99%